Reproducibility (Reliability and Agreement) of Post-exercise Hypotension - Fecchio, Rafael Yokoyama; Chehuen, Marcel; Brito, Leandro Campos; Peçanha, Tiago; Queiroz, Andréia Cristiane Carrenho; de Moraes Forjaz, Claudia Lucia (International Journal of Sports Medicine, 2017)
This study determined the reproducibility of post-exercise hypotension (PEH) calculated by the following methods: PEH_I=post-exercise BP − pre-exercise BP; PEH_II=post-exercise BP − post-control BP; and PEH_III=[(post-exercise BP − pre-exercise BP)−(post-control BP − pre-control BP)]. Twenty-five participants underwent four sessions divided in two blocks (test and retest). Each block consisted of one exercise and one control session. BP pressure was measured before and after the interventions. The presence of systematic error (paired t-tests), reliability [intraclass coefficient correlation (ICC)], and agreement [typical error (TE) and minimal detectable difference (MDD)] were evaluated. PEHs calculated by the three methods were similar between test and retest. For systolic PEH, ICC was>0.74, TE ranged from 2.6 to 4.6 mmHg and MDD from 7.2 to 12.8 mmHg for the three methods. For diastolic PEH, ICC was<0.48, TE ranged from 3.5 to 5.6 mmHg and MDD from 9.8 to 15.4 mmHg for the three methods. Thus, systolic PEH calculated by the three methods has good/excellent reliability, while diastolic PEH has fair/poor reliability. Regarding agreement, TE and MDD varied among the methods, which implies that the specific parameters given for each method should be used to estimate sample sizes for studies and the minimal individual difference considered real when comparing PEHs.
Keywords: blood pressure; exercise; recovery; measurement error; minimal detectable difference; test-retest